Independence From Parenteral Nutrition and Intravenous Fluid Support During Treatment With Teduglutide Among Patients With Intestinal Failure Associated With Short Bowel Syndrome. (23rd November 2016) - Iyer, Kishore R.; Kunecki, Marek; Boullata, Joseph I.; Fujioka, Ken; Joly, Francisca; Gabe, Simon; Pape, Ulrich‐Frank; Schneider, Stéphane M.; Virgili Casas, María Nuria; Ziegler, Thomas R.; Li, Benjamin; Youssef, Nader N.; et al.
Abstract : Background: In phase III clinical studies, treatment with teduglutide was associated with clinically meaningful reductions (≥20% from baseline) in parenteral support (PS; parenteral nutrition and/or intravenous fluids) requirements in adult patients with intestinal failure associated with short bowel syndrome (SBS‐IF). This analysis reports clinical characteristics of patients who achieved complete independence from PS during teduglutide treatment. Materials and Methods: Post hoc analysis of adult patients who achieved complete PS independence during treatment with teduglutide 0.05 mg/kg/d. Data were pooled from 5 teduglutide clinical trials (2 phase III placebo‐controlled trials [NCT00081458 and NCT00798967] and their respective extension studies [NCT00172185, NCT00930644, NCT01560403]). Descriptive statistics were used; no between‐group comparisons were performed because of the small sample size and lack of comparator. Results: Of 134 patients, 16 gained oral or enteral autonomy after a median of 5 years of PS dependence and 89 weeks of teduglutide treatment. Demographic and baseline disease characteristics varied among patients (median age, 55 years; 50% men; median baseline PS volume, 5.1 L/wk; median residual small intestine length, 52.5 cm). Most patients who achieved PS independence had colon‐in‐continuity; however, there was no significant difference in the frequency of PS independence among patients who maintained colon‐in‐continuity vs those who did not. Conclusion: Findings from this post hoc analysis suggest that oral or enteral autonomy is possible for some patients with SBS‐IF who are treated with teduglutide, regardless of baseline characteristics and despite long‐term PS dependence.